PENDEKATAN ISLAM TERHADAP KONSUMSI, TABUNGAN, DAN INVESTASI: LANDASAN TEORI DAN APLIKASI EKONOMI SYARIAH - Ervina Tri Rahayu; Nafa Faisatul Qolbi; Ilma Qurotul Aini; Rizka Khoirun Nisa; Amalia Nuril Hidayati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research discusses the relationship between consumption, saving, and investment from the perspective of Islamic economics. Unlike conventional economics, Islamic economics emphasizes spiritual values, justice, and blessings in economic activities. The purpose of this study is to examine the chapter on consumption, savings, and investment from an Islamic perspective. The method used in this study is a literature review based on sources from books and scholarly journals. The findings indicate that moderate consumption encourages increased savings and productive investments. Sharia-compliant investments, which are free from usury (riba) and speculation (gharar), play a significant role in promoting equitable economic growth. In conclusion, the interconnection between these three economic activities forms a sustainable Islamic economic system aligned with the objectives of Maqashid Sharia.